Intake of Calanus finmarchicus oil for 12 weeks improves omega-3 index in healthy older subjects engaging in an exercise programme - Wasserfurth, Paulina; Nebl, Josefine; Boßlau, Tim Konstantin; Krüger, Karsten; Hahn, Andreas; Schuchardt, Jan Philipp (British journal of nutrition, 2021)
The n-3 PUFA, EPA and DHA, play an important role in human health. As the intake of EPA and DHA from the diet is often inadequate, supplementation of those fatty acids is recommended. A novel source of n-3 PUFA is Calanus finmarchicus oil (CO) which contains fatty acids mainly bound in wax esters. To date, no data are available on the effects of long-term intake of this marine oil on n-3 PUFA blood levels. Therefore, the aim of this study was to evaluate the effect of CO on the n-3 PUFA blood levels using the omega-3 index (O3I). The data originate from a larger randomised controlled trial. For this analysis, samples from seventy-two participants (59·2 (sd 6·2) years, BMI 27·7 (sd 5·28) kg/m2) were analysed. Of those, thirty-six performed 2×/week exercise and received 2 g of CO, which provided 124 mg stearidonic acid (SDA), 109 mg EPA and 87 mg DHA daily (EXCO group), while the other group performed exercise only (EX group) and served as a control for this analysis. The O3I increased from 6·07 (sd 1·29) % at baseline to 7·37 (sd 1·10) % after 12 weeks within the EXCO group (P < 0·001), while there were no significant changes in the EX group (6·01 (sd 1·26)–6·15 (sd 1·32) %, P = 0·238). These data provide first evidence that wax ester-bound n-3 PUFA from CO can significantly increase the O3I despite relatively low EPA + DHA amounts. Further, the effects of exercise could be excluded.